Phytopharmaceuticals : potential therapeutic applications - Chauhan, Durgesh Nandini; Shah, Kamal (Hoboken, NJ : Wiley-Scrivener, 2021)
'Medicinal plants contain a variety of bioactive compounds, (also referred to as phytochemicals). in the leaves, stems, flowers and fruits. This book covers these bioactive compounds, their available sources, how the bioactive molecules are isolated from the plants, the biochemistry, structural composition and potential biological activities. Also discussed are the pharmacological aspects of medicinal plants, phytochemistry and biological activities of different natural products, ethnobotany and medicinal properties, as well as a novel dietary approach for various disease management and therapeutic potential. The importance of phytopharmaceutical of plants and potential applications in the food and pharma industries is highlighted'--
Includes bibliographical references and index.
Keywords: Medicinal plants; Phytochemicals; Pharmacognosy